Ferecides de Siros y Ferecides de Atenas. Una nueva aproximación - Pàmias, Jordi (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2005)
Scarcity of direct quotations attributed both to Pherekydes of Syros and Pherekydes of Athens does not encourage distinguishing between them on stylistic and linguistic grounds. Rather, arguments based on literary and historico cultural evidence may contribute to the «Pherekydean Question». Catasterisms, as witnessed in the work of Pherekydes of Athens, are incompatible with the archaic production of a theologian and Wundermannlike Pherekydes of Syros.